2014
DOI: 10.1371/journal.pone.0111431
|View full text |Cite
|
Sign up to set email alerts
|

Down Regulation of Wnt Signaling Mitigates Hypoxia-Induced Chemoresistance in Human Osteosarcoma Cells

Abstract: Osteosarcoma (OS) is the most common type of solid bone cancer and remains the second leading cause of cancer-related death for children and young adults. Hypoxia is an element intrinsic to most solid-tumor microenvironments, including that of OS, and is associated with resistance to therapy, poor survival, and a malignant phenotype. Cells respond to hypoxia through alterations in gene expression, mediated most notably through the hypoxia-inducible factor (HIF) class of transcription factors. Here we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…The mechanisms of attenuated β‐catenin activation are unclear. Significant oxidant stress and markedly increased free radical production in SFSG may be one reason, as many studies have shown that hypoxia or I/R injury could downregulate Wnt/β‐catenin signaling . However, Funato et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of attenuated β‐catenin activation are unclear. Significant oxidant stress and markedly increased free radical production in SFSG may be one reason, as many studies have shown that hypoxia or I/R injury could downregulate Wnt/β‐catenin signaling . However, Funato et al.…”
Section: Discussionmentioning
confidence: 99%
“…Significant oxidant stress and markedly increased free radical production in SFSG 32,40,41 may be one reason, as many studies have shown that hypoxia or I/R injury could downregulate Wnt/β-catenin signaling. 19,35,42,43 However, Funato et al showed that treatment of cells with a low dose of reactive oxygen species (ROS) induces rapid stabilization of β-catenin and a concomitant increase in the expression of endogenous Wnt target genes. 44 Therefore, we speculate that the different levels of ROS in SFSG and half-size grafts may be the reason that there is attenuated β-catenin activation in SFSG, but not in half-size liver grafts.…”
Section: Figurementioning
confidence: 99%
“…In another study, Scholten II et al reported that Wnt/βcatenin signaling is downregulated by hypoxia in osteosarcoma cells (OS), which appears to rely on both HIF-independent and -dependent mechanisms. 81 This study suggested that an inverse association between Wnt/βcatenin and HIF, but interestingly further downregulation of Wnt/βcatenin, mitigated the hypoxia-induced chemoresistance in these cells. 81 Santoyo-Ramos et al suggested even complicated interaction between Wnt/βcatenin and HIF-1.…”
Section: Hypoxia-induced Signaling Pathwaysmentioning
confidence: 67%
“…81 This study suggested that an inverse association between Wnt/βcatenin and HIF, but interestingly further downregulation of Wnt/βcatenin, mitigated the hypoxia-induced chemoresistance in these cells. 81 Santoyo-Ramos et al suggested even complicated interaction between Wnt/βcatenin and HIF-1. 82 PIn hypoxic colon cancer cells, HIF-1α promoted Wnt/βcatenin signaling, EMT, and stemness, while HIF-2α seems to negatively regulate Wnt/βcatenin signaling.…”
Section: Hypoxia-induced Signaling Pathwaysmentioning
confidence: 67%
“…Moreover, serum deprivation has been shown to result in the downregulation of the WNT/β-catenin signaling in cancer cells by upregulated Wnt3a leading to the internalization of low-density lipoprotein receptor-related protein 6, which reduces the nuclear accumulation of βcatenin [22]. The hypoxia-induced downregulation of βcatenin has been also described in human cancer cells [23,24]. Thus, serum starvation and hypoxia might have functioned cooperatively in the further inhibition of WNT/βcatenin signaling, leading to the alteration in the differentiation of the current XAV939-treated leiomyoma cells.…”
Section: Discussionmentioning
confidence: 98%